2020
DOI: 10.1002/jbmr.4751
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor B Is a Key Element in the Pathological Bone Formation of Ankylosing Spondylitis

Abstract: Enthesophyte formation plays a crucial role in the development of spinal ankylosis in ankylosing spondylitis (AS). We aimed to investigate the role of platelet-derived growth factor B (PDGFB) in enthesophyte formation of AS using in vitro and in vivo models and to determine the association between PDGFB and spinal progression in AS. Serum PDGFB levels were measured in AS patients and healthy controls (HC). Human entheseal tissues attached to facet joints or spinous processes were harvested at the time of surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Moreover, recombinant PDGFB administration enhanced enthesis cells' bone mineralization, which was evident in AS, whereas PDGFRB inhibition effectively inhibited PDGFB's capacity to trigger bone mineralization. A potential suppression of bone growth in AS may commence with pharmacological targeting of PDGFRB 131,132 . It was reported that the Wnt pathway contributes to both homeostasis and bone formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recombinant PDGFB administration enhanced enthesis cells' bone mineralization, which was evident in AS, whereas PDGFRB inhibition effectively inhibited PDGFB's capacity to trigger bone mineralization. A potential suppression of bone growth in AS may commence with pharmacological targeting of PDGFRB 131,132 . It was reported that the Wnt pathway contributes to both homeostasis and bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…A potential suppression of bone growth in AS may commence with pharmacological targeting of PDGFRB. 131,132 It was reported that the Wnt pathway contributes to both homeostasis and bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…The protocols for isolation of osteoprogenitor cells were previously reported 26–31 . Surgical bone were split into pieces using rongeur, followed by washed with 1× PBS supplemented with 1% penicillin and streptomycin (Gibco, 15140122) to remove all marrow cells and blood.…”
Section: Methodsmentioning
confidence: 99%
“…The protocols for isolation of osteoprogenitor cells were previously reported. [26][27][28][29][30][31] Surgical bone were split into pieces using rongeur, followed by washed with 1× PBS supplemented with 1% penicillin and streptomycin (Gibco, 15140122) to remove all marrow cells and blood. The bone tissue were cultured in DMEM-HG (Hyclone, SH30243.01) supplemented with 10% FBS (Gibco, 16000044) and 1% penicillin and streptomycin (Gibco, 15140122) at 37°C in 5% CO 2 conditioned incubators.…”
Section: Isolation Of Osteoprogenitor Cells and Osteoblast Differenti...mentioning
confidence: 99%
“…3A). Previous studies have shown that PDGFB was known to be a potent mitogen and chemoattractant for cells involved in wound healing and tissue regeneration, including cells critical for bone healing processes [24,25]. Then, PDGFB was chosen for further investigation.…”
Section: Linc00323 Interacted With Fusmentioning
confidence: 99%